Surgical resection of extremely rare primary giant splenic angiomyolipoma: a case report - Kaoru Sato; Fumito Saijo; Yu Katayose; Mitsuhisa Mutoh; Noriyuki Iwama; Fumie Nakayama; Hiromi Tokumura (Surgical Case Reports)
Abstract Background Angiomyolipoma is a benign mesenchymal tumor that develops commonly in the kidney and rarely in other organs. The involvement of the spleen in angiomyolipoma is extremely rare, and only one such case has been reported in the English literature. Case presentation A 27-year-old man presented with adenoid hyperplasia and bilateral palatal tonsillar hyperplasia. During the treatment for adenoid hyperplasia, a 15-cm tumor was detected in the spleen using abdominal ultrasonography and enhanced computed tomography. Partial resection of the spleen was successfully performed. A giant tumor of approximately 13 cm with a smooth surface was observed in the upper left quadrant of the abdomen. The tumor was confirmed to be continuous with the upper spleen, and there was no invasion of the other organs. The postoperative course was good, and the patient was discharged on the 7th postoperative day. The excised specimen was a smooth, extremely soft tumor measuring 123 × 120 × 82 mm. The cleaved surface of the tumor was reddish brown, and a distressing yellow color was observed. Pathological examination revealed a proliferation of mature adipocytes and an increase in the number of blood vessels of various sizes. Furthermore, spindle-shaped cell proliferation foci were visible between the adipocytes and the surrounding blood vessels. Profuse leakage of erythrocytes from the blood vessels, hemosiderin deposition, and small round cell infiltration were also noted. Immunostaining disclosed that the spindle-shaped cells were weakly positive for smooth muscle antibody and were identified as smooth muscle cells. The adipocytes and spindle cells were negative for HMB 45, Melan A, MDM, and CDK4. However, some parts of the cells were positive for estrogen and progesterone receptors. Besides, vascular endothelial cells were positive for CD31 and CD34 and negative for CD8. Based on these findings, the patient was diagnosed to have primary angiomyolipoma of the spleen. Conclusions We have reported the surgical treatment for an extremely rare case of giant splenic angiomyolipoma in a young man. Globally, this is the second report on this condition. We believe that partial splenic resection is a feasible option for the management of giant tumors.